PERANAN FISIKA DALAM BAKU MUTU BUDIDAYA - Firmansyah Bagus Saputra (Journal Sains dan Teknologi Budidaya Perairan (SINTASAN), 2024)
Physics plays an important role in determining environmental conditions suitable for aquaculture's growth and development. Helps determine the amount of water flowing in and out of the pool, how quickly the water temperature rises or falls, and how to maintain the chemical stability of the water. It is important to carry out planning analysis in aquaculture management in accordance with the Minister of Environment Regulation No. 51 concerning seawater quality standards. If the water is high tide, it will flow automatically with aquaculture. It has not been widely investigated, but this study is considered important because it has yet to be available in ministerial regulations, even though quality standards are very important in planning and managing ponds as an integral part of the economic development of coastal communities. Physics studies are needed in pond management in this country.